Arabic Conversation Problems Among Students at Prince of Songkla University: Influencing Factors and Demographic Differences - Asma Binti Abdul Rahman; Noza Aflisia; Prasert Ban Buri; Rusdee Taher; Maryam Abdul Rahman; Omar Din; Mohammad Roshimi Bin Abdullah; Ahmad Abdul Rahman (Institut Agama Islam Negeri Curup, 2026)
This study investigates the challenges faced by non-native Arabic-speaking students in developing Arabic conversational skills at Prince Songkla University, Pattani Campus, Thailand. The study aims to identify students’ perspectives on Arabic conversation problems and the factors influencing these difficulties, as well as to examine statistically significant differences based on demographic and educational variables. The study employed a descriptive-analytical approach using a questionnaire distributed to a randomly selected sample of 274 students. The findings revealed that student-related factors constituted the dominant challenges, particularly students’ low motivation to speak Arabic and lack of confidence in oral communication. Environmental factors included limited family encouragement and the absence of Arabic use within the family environment, while university-related factors involved the frequent use of local languages by lecturers and peers instead of Arabic. The study also found statistically significant differences based on academic year and participation in Arabic language activities, whereas no significant differences were found based on gender, faculty, or mother tongue. Students who actively participated in Arabic language activities demonstrated more positive responses toward Arabic conversation learning. The findings indicate that improving Arabic conversational competence requires supportive communicative environments, increased opportunities for authentic Arabic interaction, communicative teaching practices, and active participation in Arabic language programs and activities both inside and outside the classroom.